Readability, Subjective Preference and Mental Workload Studies on Young Indian Adults for Selection of Optimum Font Type and Size during Onscreen Reading - Jayeeta Banerjee, Deepti Majumdar, Madhu Sudan Pal and Dhurjati Majumdar (Al Ameen Medical College, 2011)
Font type and size characteristics play an important role in understanding the complexities of visual information in human-computer interface. India has emerged as the fastest growing personal computer (PC) user in the Asia pacific region. Studies and guidelines on the use of font type and size on screen for computer users are limited in the literature. Present work evaluates the influence of font type and size on reading on a computer screen in a group of young adults. Forty subjects volunteered for the study. Two types of fonts were used. Serif fonts included Times New Roman (TNR), Georgia and Courier New. Sans serif fonts included Arial, Verdana and Tahoma. These fonts were presented in 10, 12 and 14 point sizes. Subjects read eighteen passages (same length and reading level). Reading time, ranking and mental workload were measured. Readability was better for Serif compared to Sans serif. Reading time was minimum for Courier New 14 point. Sans serif fonts were preferred more than Serif fonts. Subjects' ranking was highest and mental workload was least for Verdana 14 point. The present study recommends using 14 point sized fonts for reading on computer screen. Courier New is recommended based on reading time while for making onscreen presentation more attractive, Verdana is recommended based on subjects' ranking and mental workload scoring.